Implementasi Kura Framework pada Purwarupa Rumah Cerdas - Muhammad Iqbal; Sabriansyah Rizqika Akbar; Bayu Priyambadha (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
One of the challenges when implementing a smart home system is the interoperability with the diversity of devices and technologies that are potentially used in an intelligent home system (Lakomiak, 2017). These challenges can be overcome by applying IoT gateways to a smart home system. IoT gateway is responsible for bridging between endpoint devices such as sensors and actuators with brokers so that these devices can send information to the broker and can be controlled by the client remotely. From that problem, Eclipse developed an IoT framework called Kura. The purpose of this study is to implement Kura on the prototype of a smart home systems and test the performance provided. To know the performance of the prototype of a smart home system built is done testing the validity of the system and calculation of the response time system. From the results of the tests conducted, it was found that in the automation cycle of publishing data from the client device to the smart device until the data returned displayed on the client device within 1 second, the system successfully perform the task and display the return to the client in accordance with the data published by the client. With the average response time in one cycle is 990.8 ms which is still less than 1 second, the performance of the intelligent home system prototype using the Kura framework can be categorized well and still accepted by the client (Neil, 2009).